2019
DOI: 10.1590/fst.28717
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of adulteration in commercial buffalo meat products by multiplex PCR assay

Abstract: Authentication of commercial buffalo meat products has become a market concern. This study intended to develop and validate a highly species-specific multiplex PCR assay for authentication of buffalo meat products. Four pairs of species-specific primers were used to target mitochondrial cytochrome oxidase O (CDO) gene. The assay generated the expected PCR products of 313, 255, 294 and 177 bp for buffalo meat, cattle meat, pork meat and duck meat, respectively. The multiplex PCR assay was sensitive enough to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…However, the tendency to mix pork meat and fat into the processed meats is more frequent in other countries due to high production of pork flesh and its cheapness. The previous study found that meat products that were declared as buffalo contained pork 7,13 . In addition, beef and mutton meat might replace in chicken, horse, and donkey meat.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the tendency to mix pork meat and fat into the processed meats is more frequent in other countries due to high production of pork flesh and its cheapness. The previous study found that meat products that were declared as buffalo contained pork 7,13 . In addition, beef and mutton meat might replace in chicken, horse, and donkey meat.…”
Section: Resultsmentioning
confidence: 99%
“…However, DNA detection technique is considered as reliable, efficient, simple and a quick method to identify meat species 6 . In previous studies, testing processed of meat products by DNA detection technique revealed the use of a label that is incorrect (7) . Since becoming aware of these issues, this work aimed to identify pork in canned meat products by detection the meat specie in it under laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of NIR spectroscopy for authentication and characterization of fats in cow and buffalo ghee (anhydrous milk fat) has been successfully proved as well (Antony et al, 2018). It is worthy to mention that there are also other promising analytical methods such as polymerase chain reaction (PCR) assay whose accuracy and reliability as authentication tools have been reported for meat product (Wang et al, 2019).…”
Section: / 73 / 8933mentioning
confidence: 99%
“…Similar techniques have also been used to assess meat’s adulteration for human consumption (see, for example, [ 113 , 114 ]). Besides, to this day, some reference materials regarding species identification have been successfully produced to test laboratory adeptness (for example, the Dem Deutschen Referenzbüro für Ringversuche & Referenzmaterialien, which organize proficiency testing schemes for the determination in animal species for food matrices such as gelatin and candy).…”
Section: Selected Instrumental Techniques and Their Applicationsmentioning
confidence: 99%